Mitochondrial aconitase 1 regulates age-related memory impairment via autophagy/mitophagy-mediated neural plasticity in middle-aged flies. - Cho, Y.H.; Kim, G.H.; Park, J.J. (Aging Cell, 2021)
Age-related memory impairment (AMI) occurs in many species, including humans. The underlying mechanisms are not fully understood. In wild-type Drosophila (w1118), AMI appears in the form of a decrease in learning (3-min memory) from middle age (30 days after eclosion [DAE]). We performed in vivo, DNA microarray, and behavioral screen studies to identify genes controlling both lifespan and AMI and selected mitochondrial Acon1 (mAcon1). mAcon1 expression in the head of w1118 decreased with age. Neuronal overexpression of mAcon1 extended its lifespan and improved AMI. Neuronal or mushroom body expression of mAcon1 regulated the learning of young (10 DAE) and middle-aged flies. Interestingly, acetyl-CoA and citrate levels increased in the heads of middle-aged and neuronal mAcon1 knockdown flies. Acetyl-CoA, as a cellular energy sensor, is related to autophagy. Autophagy activity and efficacy determined by the positive and negative changes in the expression levels of Atg8a-II and p62 were proportional to the expression level of mAcon1. Levels of the presynaptic active zone scaffold protein Bruchpilot were inversely proportional to neuronal mAcon1 levels in the whole brain. Furthermore, mAcon1 overexpression in Kenyon cells induced mitophagy labeled with mt-Keima and improved learning ability. Both processes were blocked by pink1 knockdown. Taken together, our results imply that the regulation of learning and AMI by mAcon1 occurs via autophagy/mitophagy-mediated neural plasticity.